INFLUENCE OF STRENGTHENING MATHEMATICS AND SCIENCE EDUCATION PROGRAMME ON ENHANCING TEACHING AND EVALUATION SKILLS IN BIOLOGY IN PUBLIC SECONDARY SCHOOLS IN NYAMACHE SUB-COUNTY, KISII COUNTY, KENYA - , Pamela Anyona Ameka; Simon Nyakwara (IJRDO - Journal of Social Science and Humanities Research, 2020)
Strengthening Mathematics and Science Education (SMASE) was introduced when consistent poor performance in science and mathematics became a matter of serious concern. Although poor performance in these subjects had already been accepted as the norm in some schools, the government of Kenya and other stakeholders felt there had to be an intervention. Although it is acknowledged that there are other factors contributing to the dismal performance, the government chose to focus on the teacher as the teacher is key in the curriculum implementation phase. The INSET Curriculum was thus designed to improve and strengthen the teacher’s competence in the teaching of Science and Mathematics subjects. The programme activities are centered on the ASEI (Activity, Student, Experiment, and Improvisation) & PDSI (Plan, Do, See and Improve) approach, which emphasize on learner–centered preparation and presentation of lessons. The main purpose of this study was to investigate the influence of SMASE training on performance of Biology in public secondary schools in Nyamache Sub-County, Kenya. The study focused on gathering from the respondents participating in this research. Sampled school principals and Biology teachers were involved in this research. The study established that enhanced teaching and evaluation skills positively and significantly influence performance in biology, enhanced student’s understanding in biology positive and significantly influence performance in biology, it revealed that challenges faced by school principals in managing the implementation of SMASE acquired skills in schools negatively and significantly influence the performance of learners in biology and lastly but not least the study found out that performance in biology after implementation of SMASE programme has significantly improved compared to performance before implementation of SMASE programme. In view of these findings, the study concludes that effective implementation of skills acquired in SMASE is important in schools. This means that to realize implementation of these skills in schools, school principal’s management and facilitation for the implementation of these skills must be changed and the ministry must consider retaining teachers trained through SMASE programme when effecting transfers and also consider training teachers with few teaching years so that they can be in position to handle the anticipated change in curriculum.